A comparison of two methods for eliciting contingent valuations of colorectal cancer screening. - Whynes, D; Frew, E; Wolstenholme, J (2003)
Willingness-to-pay (WTP) is being used increasingly in health technology assessment, although a number of methodological issues remain unresolved. Using data obtained from a randomised questionnaire survey, we investigated the metrical properties of two WTP formats, the open-ended question versus the payment scale, in the context of screening for colorectal cancer. Approximately, 2800 responses were analysed. Household income, attitudes toward health promotion and personal risk perceptions were the principal determinants of the nature and value of response. In comparison with the open-ended format, the payment scale achieved a higher completion rate and generated higher valuations. We believe that a framing effect is the most plausible explanation for these differences in performance. In contrast to previous findings, we do not find subjects' perceptions of the resource cost of interventions to be a convincing explanation for either their WTP values or inconsistencies between values and preferences. Although a proportion of respondents protested at the notion of valuation, the majority offer positive valuations, although typically of a lower value that non-protesters.